From Morphology to Speaking: Developing an Al-Amthilah al-Taṣrīfiyyah Companion Book for Beginner Arabic Learners - Syahrul Iswan; Asep Sunarko (Fakultas Tarbiyah Program Studi Pendidikan Bahasa Arab Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2024)
Traditional Arabic morphology instruction often enables beginner learners to memorize conjugational patterns without adequately supporting their application in meaningful language use. This study aimed to develop, validate, and evaluate a bilingual Arabic–Indonesian companion book for Al-Amthilah al-Taṣrīfiyyah that connects morphological knowledge with sentence construction and guided speaking practice. The study employed an educational research and development design integrating qualitative and quantitative approaches. It involved forty-five third-grade ibtidāʾī students at Darullughah Wadda’wah Ba‘alawi Islamic Boarding School, Bangil, East Java, Indonesia. Six students participated in a limited trial, while two experts evaluated the content and instructional design. Data were collected through classroom observation, semi-structured interviews, validation questionnaires, student responses, and pretest–posttest instruments. The developed product contained bilingual explanations, vocabulary meanings, contextual examples, learning instructions, and structured exercises organized into eight instructional units. Expert validation produced an overall feasibility score of 90.4 percent, classified as very good. Student feedback prompted revisions to typography, color, images, and instructional presentation. Quantitative findings showed that the mean score increased from 67.78 (SD = 28.50) on the pretest to 89.24 (SD = 18.52) on the posttest. The difference was statistically significant, t(44) = 5.59, p < .001, with a large within-participant effect, dz = .83. These findings indicate that the companion book effectively strengthened learners’ functional morphological mastery. The study contributes a contextual model for transforming traditional ṣarf memorization into structured linguistic practice supporting beginner Arabic speaking instruction. Because the assessment primarily measured written morphological achievement, further research should examine transfer to spontaneous oral performance.